“Everything Is Easy for Me…” Ethnological Research of Consciousness - Šmitienė, Giedrė (Tautosakos darbai, 2017)
Veronika’s practical ways of dissociating from troubles merit special attention. The author interprets her byword baika (‘trifle’) as used to remind of the emptiness of everything that takes place. Her characteristic abstaining from judging other people’s actions is defined as an unjudging amiability. This typical abstaining also involves disinclination to create systems or subordinate all phenomena to the requirements of a single one. Abstaining from judgement rests on her feeling that “there is more” to things than could be gained from a single situation.Although the above-mentioned qualities may seem as pertaining to an indifferent or passive consciousness, this is disproved by Veronika’s obvious capacity of making decisions. Describing the way of her decision making the author discloses that decisions are seen in the situation. Here, the concept of tacit and secret decisions by Maurice Merleau-Ponty comes particularly handy. It is easier to perceive such seen decisions after having acknowledged that consideration, decision, and selection is possible even for implicit self.All these qualities are permeated by the expression of being content. Being content rests on an easy sense of being appropriate. The sense of easiness is achieved by allowing the life to be the way it is.
Keywords: -